Synthesis and electrical transport properties of Er1-xScxNiSb semiconducting solid solution - Romaka, L.; Stadnyk, Yu.; Romaka, V.A.; Klyzub, P.; Pashkevych, V.; Horyn, A.; Garanyuk, P. (Physics and Chemistry of Solid State, 2021)
Samples of Er1-xScxNiSb (x = 0–0.10) solid solution were synthesized by an arc-melting and the effect of doping by Sc atoms on the electrokinetic and energetic characteristics of the half-Heusler ErNiSb phase was investigated. It was established that at the studied concentrations the main carriers of electricity in the Er1-xScxNiSb semiconductor are holes. It was shown that doping of p-ErNiSb compound by Sc atoms introduced by substitution of Er atoms in 4a position is accompanied by the occupation of presented vacancies in position 4a, which leads to the reduction and elimination of structural defects of acceptor nature and corresponding acceptor band. The concentration ratio of ionized acceptors and donors generated in Er1-xScxNiSb determines the position of the Fermi level and the mechanisms of electrical conduction. The investigated solid solution Er1-xScxNiSb is a promising thermoelectric material.